A new class of 5‐HT2A/5‐HT2C receptor inverse agonists: Synthesis, molecular modeling, in vitro and in vivo pharmacology of novel 2‐aminotetralins. (7th March 2022) - Casey, Austen B.; Mukherjee, Munmun; McGlynn, Ryan P.; Cui, Meng; Kohut, Stephen J.; Booth, Raymond G.
Abstract : Background and Purpose: The 5‐HT receptor subtypes 5‐HT2A and 5‐HT2C are important neurotherapeutic targets, though, obtaining selectivity over 5‐HT2B and H1 receptors is challenging. Here, we delineated molecular determinants of selective binding to 5‐HT2A and 5‐HT2C receptors for novel 4‐phenyl‐2‐dimethylaminotetralins (4‐PATs). Experimental Approach: We synthesized 42 novel 4‐PATs with halogen or aryl moieties at the C(4)‐phenyl meta ‐position. Affinity, function, molecular modeling and 5‐HT2A receptor mutagenesis studies were performed to understand structure–activity relationships at 5‐HT2 ‐type and H1 receptors. Lead 4‐PAT‐type 5‐HT2A /5‐HT2C receptor inverse agonists were compared with pimavanserin, a selective 5‐HT2A /5‐HT2C receptor inverse agonist approved to treat Parkinson's disease‐related psychosis, in the mouse head twitch response and locomotor activity assays, models relevant to antipsychotic drug development. Key Results: Most 4‐PAT diastereomers in the (2 S, 4 R )‐configuration bound non‐selectively to 5‐HT2A, 5‐HT2C and H1 receptors, with >100‐fold selectivity over 5‐HT2B receptors, whereas diastereomers in the (2 R, 4 R )‐configuration bound preferentially to 5‐HT2A over 5‐HT2C receptors and had >100‐fold selectivity over 5‐HT2B and H1 receptors. Results suggest that G238 5.42 and V235 5.39 in 5‐HT2A receptors (conserved in 5‐HT2C receptors) are important for high affinity binding, whereas interactions with T194 5.42 and W158 4.56 determine H1 receptor affinity. The 4‐PAT analog (2 S, 4 R )‐4‐(4'‐(dimethylamino)‐[1, 1'‐biphenyl]‐3‐yl)‐ N, N ‐dimethyl‐1, 2, 3, 4‐tetrahydronaphthalen‐2‐amine, (2 S, 4 R )‐2k, a potent and selective 5‐HT2A /5‐HT2C receptor inverse agonist, had activity like pimavanserin in the mouse head twitch response assay but was distinct in not suppressing locomotor activity. Conclusions and Implications: The novel 4‐PAT chemotype can yield selective 5‐HT2A /5‐HT2C receptor inverse agonists for antipsychotic drug development by optimizing ligand–receptor interactions in transmembrane domain 5. Chirality can be exploited to attain selectivity over H1 receptors, which may circumvent sedative effects. Abstract :